2013
DOI: 10.12697/akut.2013.19.03
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among repeated sprint tests and aerobic fitness in adolescent tennis players

Abstract: Th e aim of this study was to determine the performance indices (ideal sprint time -IS, total sprint time -TS, and performance decrement -PD) of two repeated sprint test (RST) and to examine their relationships with the aerobic fi tness of young tennis players. Fift een young (age 14.7±1.0 yrs) tennis players performed three tests: an aerobic power test (20 m shutt le run), and two diff erent RST protocols (12×20 m and 12×10 m runs). Peak heart rate was signifi cantly higher in the 20 m protocol compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Performance decrement (PD) score was calculated as a measure of fatigue index which is as follows: PD = [(TS/IS) × 100] – 100 where, TS: Total time, calculated as the sum total of all 12 sprints; IS: Ideal time, calculated as the fastest time among all the sprints multiplied by 12. 18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance decrement (PD) score was calculated as a measure of fatigue index which is as follows: PD = [(TS/IS) × 100] – 100 where, TS: Total time, calculated as the sum total of all 12 sprints; IS: Ideal time, calculated as the fastest time among all the sprints multiplied by 12. 18…”
Section: Methodsmentioning
confidence: 99%
“…Total time, calculated as the sum total of all 12 sprints; IS: Ideal time, calculated as the fastest time among all the sprints multiplied by 12. 18…”
Section: Upper Body Stabilitymentioning
confidence: 99%
“…The goal of RST is to improve the Repeated sprint ability (RSA). One study in tennis showed significant correlations between performances in RSA tests and VO2max (Tsiprun et al, 2013). The aerobic energy system is an important determinant in recovery rate from intense activity and assists in power output maintenance during the RST.…”
Section: Repeated Sprint Training (Rst)mentioning
confidence: 99%